Martin Luther King, Jr. and the image of God - Wills, Richard W. (Oxford University Press, 2009)
Historical explication -- The historical context -- The host of witnesses -- Theological meditation -- King as critical thinker -- King among theologians -- Theological implications -- Practical application -- Beloved community -- Beloved community and beyond